Pathways from childhood cumulative risk to criminal conviction - Solomon, Starr (DigitalCommons@UNO, 2016)
This study examines pathways from childhood cumulative risk to criminal offending in a Finnish birth cohort. Consistent with the core assumption of the cumulative risk perspective, we find a strong association between the number of childhood risk factors and the odds of felony conviction in emerging adulthood. Drawing on the social development model, we consider three adolescent outcomes as possible mediators and moderators of the observed association: substance misuse, school failure, and general problem behavior. We examine the hypothesized pathways by estimating structural equation models using data from the 1986 Northern Finland Birth Cohort Study. The practical purpose of this research is to specify modifiable risk processes at the adolescent stage of development in order to prevent crime among children at risk.